2010
DOI: 10.1111/j.1471-8847.2009.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Tourism in Argentina: Clinic Accreditation and Its Implications for Consumers, Health Professionals and Policy Makers

Abstract: (224 words)A subcategory of medical tourism, reproductive tourism has been the subject of much public and policy debate in recent years. Specific concerns include the exploitation of individuals and communities, access to needed health care services, fair allocation of limited resources, and the quality and safety of services provided by private clinics. To date, the focus of attention has been on the thriving medical and reproductive tourism sectors in Asia and Eastern Europe; there has been much less conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…Cross‐border PGD have been observed in many parts of the world for conditions of variable severity, penetrance, and time of manifestation . The international offer on the Internet of PGD services has also been noticed as well as cross‐border traveling for non‐directive genetic counseling, an important feature of PGD services .…”
Section: Resultsmentioning
confidence: 99%
“…Cross‐border PGD have been observed in many parts of the world for conditions of variable severity, penetrance, and time of manifestation . The international offer on the Internet of PGD services has also been noticed as well as cross‐border traveling for non‐directive genetic counseling, an important feature of PGD services .…”
Section: Resultsmentioning
confidence: 99%
“…Their interpretations of the drawings as ber to 100,000 (38). In their article on reproductive well as the interviews were conducted in Spanish tourism, Smith et al (42) identified Argentina as and audio-recorded. The interviews were carried "the latest 'new player' in the medical tourism out in the facilities of Fundación Natalí Dafne industry" and highlighted the fact that one of the Flexer (FNDF), a local nongovernmental organizareasons for the increase in medical tourists was the tion focused on pediatric oncology treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, chronic understaffing and a lack of sufficient fiIn Argentina, the medical application for PGT in the public health care and social security system 9 is still quite limited, nor are there well developed public policies or regulations governing the use of these technologies (19,20). Nonetheless, private access to such services and other reproductive technologies is relatively easy (through private clinics) and Argentinean professionals employ the same techniques as their colleagues in developed countries (20,21) 10 . This shows that there is at least some degree of acceptability of these technologies by the Argentinean public, and by health professionals.…”
Section: An Ethical Hta In Argentina: the Example Of Prenatal Geneticmentioning
confidence: 99%